Analisis Rasio Keuangan dalam Menilai Tingkat Kesehatan Bank Badan Usaha Milik Negara (BUMN) pada Saat Pandemi Covid-19 - Riftiasari, Dinar (Jurnal Informatika Ekonomi Bisnis, 2023)
State-Owned Enterprise Banks (BUMN) as financial institutions play an important role in strengthening the national economy at the time of the Covid-19 pandemic when the economic conditions were not good so banking performance needed to be observed by looking at financial reports as indicators in assessing financial performance using ratios so that can be assessed how the level of health of the Bank during the Covid-19 pandemic. This study aims to determine the financial performance of BUMN Banks from the aspects of Risk Profile, Good Corporate Governance (GCG), Earning, and Capital in assessing the soundness of BUMN Banks through a risk approach (Risk-Based Bank Rating) or known as the Risk-Based Bank Rating method (Risk-Based Bank Rating). RGEC). This research method is descriptive analysis with secondary data. The population of this study is state-owned banks listed on the Indonesia Stock Exchange during the Covid-19 pandemic from 2019 to 2022. Sampling was determined based on the purposive sampling method, namely four state-owned banks, namely Bank Mandiri, Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), and the State Savings Bank (BTN). The analytical method in this study is the RGEC ratio method consisting of the Risk Profile using the Non-Performing Loan (NPL) ratio and the Loan to Deposit Ratio (LDR), GCG using the self-assessment system, earnings using the Return On Assets (ROA) ratio and Net Interest Margin ( NIM), and on the Capital aspect using the Capital Adequacy Ratio (CAR). The analysis of the RGEC method shows that the assessment of the soundness level of BUMN Banks during the Covid-19 pandemic for the 2019-2022 period was at composite 1 (Pk-1) with a very healthy predicate even though in 2020 it was at composite 2 (PK-2) with a healthy predicate.